2002
DOI: 10.1002/psc.399
|View full text |Cite
|
Sign up to set email alerts
|

Study of the yeast Saccharomyces cerevisiae F1FO‐ATPase ε‐subunit

Abstract: The yeast Saccharomyces cerevisiae F1F0-ATPase epsilon-subunit (61 residues) was synthesized by the solid-phase peptide approach under both acidic and basic strategies. Only the latter strategy allowed us to obtain a pure epsilon-subunit. The strong propensity of the protein to produce few soluble dimeric species depending on pH has been proved by size-exclusion chromatography, electrophoresis and mass spectrometry. A circular dichroism study showed that an aqueous solution containing 30% trifluoroethanol or 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] peptide displayed the lowest deuterium incorporation (Figure 5a). These data are in full agreement with the existence of an ␣-helix for the [13][14][15][16][17][18][19][20][21][22][23] region in the 3-D structure of the bovine subunit of ATPase [17].…”
Section: Solvent Accessibility In F1-atpase Complexsupporting
confidence: 80%
See 1 more Smart Citation
“…The [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] peptide displayed the lowest deuterium incorporation (Figure 5a). These data are in full agreement with the existence of an ␣-helix for the [13][14][15][16][17][18][19][20][21][22][23] region in the 3-D structure of the bovine subunit of ATPase [17].…”
Section: Solvent Accessibility In F1-atpase Complexsupporting
confidence: 80%
“…When increasing amounts of acetonitrile were mixed with D 2 O, the number of exchanged amide protons diminished: 52 deuterons were incorporated after an incubation in D 2 O with 20% of acetonitrile, 47 deuterons after incubation in D 2 O with 30% acetonitrile and 44 deuterons after an incubation in D 2 O with 40% acetonitrile (Figure 3c to e). In parallel to these experiments, a sample of subunit obtained by solid phase synthesis [21] was analyzed by circular dichroism (CD) with an increasing concentration of acetonitrile. This study (data not shown) indicated that subunit is mostly non-structured in neat water, and that an increase of acetonitrile concentration from 0 to 40% results in an increased ␣-helical structuration for this polypeptide.…”
Section: Effect Of Subunit Secondary Structure On Deuterium Labelingmentioning
confidence: 99%